Development of Arduino-Based Elevator Learning Media to Enhance Scientific Reasoning Skills in Mechanical Energy - Wika Aryani Sinulingga; Dedy Hamdani; Tiara Hardyanti Utama (CV. Media Inti Teknologi, 2026)
Background: Physics education, particularly in mechanical energy topics, often faces challenges such as low conceptual understanding and limited scientific reasoning skills. These issues are frequently associated with the lack of interactive and technology-enhanced learning media that enable students to engage with real-time data and experimental visualization.Aims: The aim of this study is to provide interactive learning media based on the Arduino Uno using an elevator system, evaluate its feasibility, and examine its effectiveness in enhancing students’ scientific reasoning skills, particularly control of variables, hypothetical–deductive reasoning, and learning engagement.Method: This study used the ADDIE process (analysis, design, development, implementation, and evaluation) to conduct research and development (R&D). Data were gathered using needs analysis questionnaires, expert validation sheets, two-tier multiple-choice tests (pretest–posttest), and student response questionnaires. The N-Gain approach was used to examine how students' scientific reasoning abilities improved.Results: The implementation of the developed learning media was followed by a significant increase in students’ scientific reasoning scores, with the average score increasing from 32 on the pretest to 88 on the posttest, resulting in an N-Gain score of 0.82 (high category). Additionally, the developed learning media received very positive student responses (94.6%), indicating high usability and engagement.Conclusion: The implementation of the Arduino-based interactive learning media using an elevator system was associated with improvements in students’ understanding of mechanical energy concepts and scientific reasoning skills, particularly in controlling variables and drawing evidence-based conclusions, while also providing an engaging and technology-supported learning experience.